edation and Analgesia Practice in Pediatric Intensive Care Units OF Cairo University Children Hospitals - Ahmed Ali Ahmed Gomaa; Noha Hassan Elanwar (2022)
(3ZGdkHG eG jMJGL eQVi GdCWaGd GdeUGHjf HCeQGV NWjQI Edi ELQGAGJ WHjI eYbOI , hJghjI ejcGfjcjI , hCde , hGfaUGd Yf CSQge , hGNJHGQGJ heQGbHI LGFQI Jejd Edi Cf Jchf eDdeI heKjQI ddbdb , eeG jSJdRe JhajQ GdeScfGJ hGdJNOjQ dJbdjd GdGSJLGHI ddVZW(B. (3jecf Cf jchf JMbjb GdeRjL GdCeKd ef GdJScjf GdefGSH hGdJNOjQ GdefGSH CekQG UYkHG ddZGjI aj eLJeY GdeQVi(B. (3dbO gOafG Edi JMdjd GdCSGdjH GdMGdjI aj eeGQSGJ GdJNOjQ hGdJScjf hGdGfSMGH Hjf hMOGJ GdYfGjI GdeQcRI ddCWaGd aj eSJTajGJ GdCWaGd HLGeYI GdbGgQI , dGcJTGa GfJTGQ GdBKGQ GdSdHjI ddJNOjQ GdeaQW hGdJNOjQ GdZjQ LjO aj eQVi GdCWaGd GdeUGHjf HCeQGV NWjQI hdJWhjQ Odjd ehMO eYJeO dJNOjQ hGdeScfGJ(B. (3GSJYQVJ OQGSI hUajI eSJbHdjI (B80 (3eQjkVG ef GdCWaGd Je bHhdge aj hMOGJ GdYfGjI GdeQcRI ddCWaGd HeSJTajGJ GdCWaGd HLGeYI GdbGgQI Ydi eOi (B6 (3CTgQ ef jhdjh (B2021 (3Edi jfGjQ (B2022 (3dJMdjd GdCSGdjH GdMGdjI aj eeGQSGJ GdJNOjQ hGdJScjf hGdGfSMGH Hjf hMOGJ GdYfGjI GdeQcRI ddCWaGd HeSJTajGJ GdCWaGd HLGeYI GdbGgQI(B. .s
Thesis (M.Sc.)-Cairo University - Faculty of Medicine - Department of Pediatrics
Bibliography: p. 112-120.
Keywords: Pediatrics; sedation